Smart metering: A water-saving solution? Consider communication strategies and user perceptions first. Evidence from a French case study. (June 2018) - Montginoul, Marielle; Vestier, Arnaud
Abstract: Smart water meters are increasingly being installed by French water utility companies and made available to users free of charge. However, households are not taking advantage of this technology in spite of the benefits it theoretically offers. This article investigates factors that may explain this technology low adoption rate, focusing on the first two steps in the process of adoption: providing information and fostering good intentions. It describes a natural field experiment conducted in a residential suburb in which 261 households were officially informed about the new smart metering service and 77 of them were then surveyed to identify potential barriers to the adoption of smart meters. We analyse the prevailing social representations of the words "water" and "smart metering". Although respondents seem more interested in, than opposed to, this new technology, its adoption rate remains low, particularly among heavy water consumers and flat renters. Highlights: A low adoption rate of smart metering service by French households. No unified social representation for the concepts "water" and "smart metering". Smart metering viewed in a positive light by French households. Families with gardens and apartment renters more likely to register for smart meter services.